Pathwise superreplication via Vovk’s outer measure - Beiglböck, M; Cox, A; Huesmann, M; Perkowski, N; Prömel, D (Springer Verlag, 2017)
Since Hobson’s seminal paper (Hobson in Finance Stoch. 2:329–347, 1998), the connection between model-independent pricing and the Skorokhod embedding problem has been a driving force in robust finance. We establish a general pricing–hedging duality for financial derivatives which are susceptible to the Skorokhod approach. Using Vovk’s approach to mathematical finance, we derive a model-independent superreplication theorem in continuous time, given information on finitely many marginals. Our result covers a broad range of exotic derivatives, including lookback options, discretely monitored Asian options, and options on realized variance.